Text on Book Cover: Blurb as a Genre - E. A. Zoidze (Научный диалог, 2024)
This article examines the annotation to book editions as a genre of publishing discourse. The aim is to provide an overview of the existing linguistic understanding of the genre’s characteristics, its functional-pragmatic communicative specificity, as well as the features related to the linguistic and cultural traditions of book publishing. The material consists of scientific articles and monographs in Russian and English published from the early 2000s to the present, selected based on keywords. The first review of the degree of research and current directions in the study of the declared genre revealed a problem of an unsettled terminological designation of this genre both in domestic and foreign practice. An approach to differentiating existing terms is proposed and justified. The functions of texts in the genre of publishing annotation are summarized and systematized, with the functional duality of informing and persuasive impact proposed as the foundation. A small number of comparative and diachronic studies were identified, the results of which would be useful for justifying the ongoing transformation process within the studied genre, according to some linguists. The conclusion is drawn that the annotation to book editions is shifting from being a reference apparatus to the realm of marketing communication, advertising, and book promotion.